Analisis Pengaruh Faktor Harga Produk Dan Kualitas Produk Terhadap Brand Attitude Melalui Brand Awareness Sebagai Variabel Intervening (Studi Pada Konsumen Restoran & Cafe Waroeng Redjo di Kota Kediri) - Adimas Ryandaru; Muhammad Ridwan Basalamah; Rahmawati Rahmawati (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract The purpose of this research is to find out and analyze the Product Price and Product Quality Factors on Brand Attitudes through Brand Awareness as an Intervening Variable. In measuring this variable, the dependent variable is brand, the independent variable is product price and product quality, while the intervention variable is brand awareness. In this study, the type of research used was quantitative research with a descriptive approach. Quantitative research method is one type of research whose specifications are systematic, well-planned and clearly structured from the beginning to the making of the research design. The method used in managing the data using multiple linear regression analysis tool through the SPSS program. The data used are primary data as well as secondary data obtained by using interview techniques, questionnaires, direct and indirect observations. The sample in this study is unknown, so in this study using the Maholtra formula with details of 17 indicators x 5 = 85. From the processing data, it is found that product price and product quality have a direct effect on brand awareness, product price and product quality have a direct effect on brand attitude., Brand awareness has a direct effect on brand attitude., and product price and product quality have an indirect effect on brand attitude through brand awareness as an intervention. Keywords: Brand Atitude, Product Price, Product Quality, And Brand Awareness.